2020
DOI: 10.1101/2020.07.07.191452
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dimeric prion protein ligand activates Adgrg6 but does not rescue myelinopathy of PrP-deficient mice

Abstract: AbstractThe adhesion G-protein coupled receptor Adgrg6 (formerly Gpr126) is instrumental in the development, maintenance and repair of peripheral nervous system myelin. The prion protein (PrP) is a potent activator of Adgrg6 and could be used as a potential therapeutic agent in treating peripheral demyelinating and dysmyelinating diseases. We designed a dimeric Fc-fusion protein comprising the myelinotrophic domain of PrP (FT2Fc), which activated Adgrg6 in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(65 reference statements)
1
0
0
Order By: Relevance
“…We have previously described that Prnp ZH3/ZH3 mice exhibit an early upregulation of repair Schwann cell markers in sciatic nerves, which probably represents an early sign of the peripheral nerve disease (26). In the present study, we confirmed that the 2-3 months old Prnp ZH3/ZH3 mice undergoing crush injury showed a two-fold upregulation of GFAP in their uninjured sciatic nerves when compared to WT mice.…”
Section: Discussionsupporting
confidence: 88%
“…We have previously described that Prnp ZH3/ZH3 mice exhibit an early upregulation of repair Schwann cell markers in sciatic nerves, which probably represents an early sign of the peripheral nerve disease (26). In the present study, we confirmed that the 2-3 months old Prnp ZH3/ZH3 mice undergoing crush injury showed a two-fold upregulation of GFAP in their uninjured sciatic nerves when compared to WT mice.…”
Section: Discussionsupporting
confidence: 88%